Beneficial prenatal levodopa therapy in autosomal recessive guanosine triphosphate cyclohydrolase 1 deficiency - Brüggemann, Norbert; Opladen, Thomas (Archives of neurology, 2012)
Objective: To report the first prenatal dopaminergic replacement therapy in autosomal recessive (AR) guanosine triphosphate cyclohydrolase 1 (GTPCH) deficiency without hyperphenylalaninemia. Design Case reports, literature review, and video presentation. Setting: University of Lübeck, Lübeck, Germany. Patients: Two boys from a consanguineous family. Main Outcome Measures: Physical and mental development as a function of replacement initiation. Results: The older sibling presented with typical features of AR GTPCH deficiency due to a homozygous mutation in the GCH1 gene with proven pathogenicity. Levodopa treatment was initiated at age 10 months and resulted in a distinct motor improvement. However, mental development was delayed. In the younger sibling, prenatal replacement therapy was initiated after a prenatal diagnosis of AR GTPCH deficiency was made. At age 17 months, both motor and mental development were normal for his age. Conclusions: This report highlights the importance of an early diagnosis, including prenatal diagnosis, of complex dopa-responsive extrapyramidal syndromes. Prenatally initiated dopaminergic replacement therapy is beneficial and thus justified in AR GTPCH deficiency, allowing prevention of significant impairment of mental abilities.